Peran Pemuda dalam Mewujudkan Demokrasi Digital: Analisis Praktik Komunikasi Politik di Media Sosial - Turahmi, Hanifah; Azizah, Zahara; Mutia, Cut Eka (Sagita Academia Journal, 2025)
The development of digital technology has transformed political communication patterns in Indonesia and positioned youth as key actors within the virtual public sphere. In the context of politics and human resource management (HRM), young people represent strategic human resources who play a crucial role in safeguarding collective interests through active participation in political processes. However, in reality, many young individuals tend to distance themselves from politics due to widespread misconduct and poor political practices in Indonesia. This stands in contrast to the political perspectives of Aristotle and Prof. Miriam Budiarjo, who view politics as an effort to achieve the common good through the formulation and attainment of collective goals. This study employs a literature review method to analyze the role of youth in fostering digital democracy through political communication practices on social media. The review also discusses how political parties, political education, and digital literacy can enhance political awareness and participation among young people. The findings indicate that youth hold a critical role in building a strong democratic system, whether through public issue discussions, digital campaigns, or policy advocacy. However, their engagement on social media has not been fully effective due to challenges such as misinformation, polarization, and low levels of political literacy. These findings highlight the importance of strengthening political education and digital literacy for young people strategy to build a healthy, inclusive, and sustainable digital democracy, while ensuring their active participation in shaping the nation’s future.